Factors related to online game addiction among adolescents - Ramadan Aji Pangestu; Miranti Dea Dora; Resa Livia Nica (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Online game addiction among adolescents that affects academic, psychological, and social aspects. The increasing use of the internet and the intensity of gaming have caused some adolescents to experience difficulties in controlling their playing time. Purpose: To determine the relationship between self-control, learning motivation, peer influence, and sleep quality with online game addiction among students. Method: This research employed a quantitative approach with a cross-sectional design. The sample consisted of 288 respondents selected using purposive sampling technique. Data were collected using questionnaires and analyzed using the chi-square test. Results: The results showed that there were significant relationships between self-control (p=0.001), learning motivation (p=0.001), and peer influence (p=0.001) with online game addiction. Meanwhile, sleep quality was not significantly related (p=0.846). Conclusion: It can be concluded that self-control, learning motivation, and peer influence are factors related to online game addiction. Suggestion: Promotive and preventive efforts in the school environment are needed to reduce excessive gaming behavior.